The love con - Glass, Seressia (Jove, 2021)
"He's cosplaying as her boyfriend but their feelings for each other are real in this romantic comedy from Seressia Glass. Sometimes Kenya Davenport believes she was switched at the hospital-how else could a lover of anime, gaming, and cosplay come from STEM parents? Still, Kenya dreams of being able to turn her creative hobby into a career. She finally has a chance to make it big when she joins the reality show competition Cosplay or No Way. There's just one catch: the challenge for the final round is all about iconic pairs, and the judges want the contestants' significant others to participate. Unfortunately, Kenya is as single as can be at the moment. Luckily her best friend, Cameron Lassiter, agrees to be her fake boyfriend for the show. Role-playing a couple in love will force them to explore what they're hiding under the mask of friendship. Can Kenya and Cam fake it until she makes it, or will she be real about her feelings, knowing it could cost her the best friend she's ever had?"--